Simplification of application operations using cloud and DevOps - Anshu Premchand; M. Sandhya; Sharmila Sankar (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In our experience of having worked with financial institutions for over 19 calendar years, we have seen that application development, maintenance and operations teams have a very silo-ed existence. In today's ever more fluid market, it is imperative for these teams to be very agile in their response to business needs. While development teams are trying to adopt agile and devops practices, operations and maintenance teams are sometimes forgotten in this transformation journey even though they play a very crucial role in managing customer facing systems. In this paper, we focus on application operations for their simplification, outline the post production challenges faced by the operations teams, assistance required from the development teams and need for coordination & harmony between application development and operations teams. We use the example of a financial organization where we are currently helping in simplification of application support processes using two key levers of cloud and devops adoption to highlight the path to simplification. We outline the solution levers we used, solution tenets, solution approach and considerations. We also share a target state model and regulated key functions & activities within the model as well as an interim operating model and a target operating model.